Right dose of NPK hydrogel concentration improves the growth of spinach (Amaranthus hybridus L.) - Imas Dewi Rani; Ahmad Mulyadi; Mia Nurkanti (Bioma : Berkala Ilmiah Biologi, 2026)
The productivity of horticultural crops is highly dependent on the availability of balanced nutrients, particularly nitrogen (N), phosphorus (P), and potassium (K). However, conventional fertilization is often inefficient due to nutrient leaching. One innovation to improve fertilization efficiency is the use of hydrogel as a slow-release nutrient medium. This study aims to investigate the effect of varying concentrations of sodium alginate-based NPK (16:16:16) hydrogel fertilizer on the growth parameters of spinach (Amaranthus hybridus L.). The study was conducted in the greenhouse of the Biology Education Program at the Faculty of Education and Teacher Training, Pasundan University, over 21 days using a Completely Randomized Design (CRD) with seven treatments: negative control, hydrogel NPK concentrations of 3.4%, 4.4%, 5.4%, 6.4%, 7.4%, and positive control (fertilizer without hydrogel). The observed parameters included the number of leaves, plant height, and stem diameter. Data were analyzed using normality tests, homogeneity tests, one-way ANOVA, and DMRT post-hoc tests with the assistance of SPSS version 29. The results showed that the treatment with a 5.4% concentration yielded the best results significantly for all three parameters: number of leaves (5.25 leaves), plant height (11.525 cm), and stem diameter (0.1748 cm). In conclusion, the 5.4% NPK hydrogel formulation is the most effective in promoting optimal and efficient growth of spinach plants.